A consequential assessment of changes in greenhouse gas emissions due to the introduction of wheat straw ethanol in the context of European legislation. (1st February 2018) - Buchspies, Benedikt; Kaltschmitt, Martin
Graphical abstract: Highlights: The shift from 1st generation to 2nd generation bioethanol from straw is assessed. Resulting GHG emissions are evaluated in the context of European legislation. Emissions might increase if 2nd generation ethanol replaces 1st generation ethanol. A detailed analysis of land-use change mechanisms confirms results. Consequently, proposed EU legislation might provoke unintended consequences. Abstract: Until today, first generation (1G) biofuels dominate the market for alternative fuels. The European Commission decided to cap 1G biofuels and promote second generation (2G) biofuels with the intention to reduce greenhouse gas (GHG) emissions, to limit the competition of food, feed and biofuels, as well as to improve societal approval. The assessment of consequences entailed to a shift from 1G to 2G biofuels is required to judge whether such a shift is advisable or not. According to the renewable energy directive (RED), GHG savings, need to be determined for all biofuels. By the end of 2020, fuel blends need to achieve a GHG reduction of 6%. Thus, GHG savings will determine the quantity of biofuel to be blended with fossil fuels and thereby eventually define the demand for biofuels. In this paper, the consequences of a shift from a 1G to a 2G biofuel is assessed by the example of bioethanol from wheat grains and straw. In total, three concepts of 2G ethanol production from wheat straw are considered: fermentation of C6-sugars with (1) co-production of feed, (2) coupled with biogas production and (3) co-fermentation of C5- and C6-sugars with co-production of feed. To determine the effect of the introduction of 2G ethanol, GHG savings according to RED are calculated first, and, in a second step, consequences of the shift from 1G to 2G ethanol are assessed by accounting for substitution mechanisms and emissions from direct and indirect land-use change (LUC). GHG savings of these 2G concepts according to RED methodology range from 103 to 105%. The shift from 1G ethanol to these 2G concepts is assessed by two scenarios: (1) additional production of 2G ethanol and (2) the replacement of 1G ethanol by 2G ethanol. Results indicate that GHG emissions decrease in scenario 1 if all surplus ethanol replaces fossil fuels. Under the given assumptions, the reduction in emissions ranges from 9.0 to 12.1 kg CO2 -eq./GJ ethanol-gasoline blend. If 1G ethanol is replaced by 2G ethanol, GHG emission increase in a range from 7.5 to 16.5 kg CO2 -eq./GJ fuel blend. This is mainly due to the provision of feed that needs to be supplied as a consequence of the shift in production: 1G ethanol production provides a high protein feed that needs to be provided by other means. Hence, the main driver for an increase in emissions is the provision of soybean meal and entailed emissions from LUC. A sensitivity analysis shows that these results are robust regarding input parameters and LUC assumptions. These findings point out that it is of utmost importance to assess changes induced by the introduction of novel fuels rather than assessing them isolated from market conditions. Based on these findings, it can be concluded that current and proposed legislation might trigger effects opposed to those intended.